Curriculum development: designing, implementing, and evaluating an ESAP course for students of the Department of Agricultural Sciences, Biotechnology and Food Science at the Cyprus University of Technology - Kakoulli-Constantinou, Elis (My University, 2009)
This paper deals with the design, implementation, and evaluation of an ESAP (English for Specific Academic Purposes) course for students of the Department of Agricultural Sciences, Biotechnology and Food Science at the Cyprus University of Technology (CUT). The students were all first year Greek-Cypriot and Greek university students having passed an EAP (English for Academic Purposes) course in the first Semester of their studies, which focused on general language and academic skills. The whole curriculum development process is revealed and all the stages of the development, implementation, monitoring and evaluation of the language programme are described. More specifically, the context is set, the techniques which were followed for analysing the learners’ needs are described, the aims and objectives determined are mentioned, the content and tasks as well as the materials developed are described, and the techniques used for evaluating the course are also set out. Despite the fact that the students were all native speakers of Greek, the effort was to design a curriculum which had a multi-cultural dimension in terms of certain topics and tasks. Therefore, in many cases students had to investigate and report the situation in other countries of the world, e.g. prepare PowerPoint presentations about agriculture in different European countries, investigate and classify the types of cattle which exist in different parts of the world etc. Even though this ESAP course was successful, curriculum renewal and change is always necessary after the completion of any educational programme. Thus, the paper finishes with suggestions about how the curriculum for the specific course can be renewed. Special emphasis is given on the process of needs analysis, which should become more comprehensive for better results. In this way a more effective setting of aims and objectives, selection and grading of content, materials development and teaching practices can be achieved.
Keywords: English for Specific Academic Purposes